Understanding the Virulence of Staphylococcus pseudintermedius: A Major Role of Pore-Forming Toxins - Maali, Yousef; Badiou, Cédric; Martins-Simões, Patrícia; Hodille, Elisabeth; Bes, Michele; Vandenesch, François; Lina, Gérard; Diot, Alan; Laurent, Frederic; Trouillet-Assant, Sophie (Frontiers in Cellular and Infection Microbiology, 2018)
Staphylococcus pseudintermedius is responsible for severe and necrotizing infections in humans and dogs. Contrary to S. aureus, the pathophysiological mechanisms involved in this virulence are incompletely understood. We previously showed the intracellular cytotoxicity induced after internalization of S. pseudintermedius. Herein, we aimed to identify the virulence factors responsible for this cytotoxic activity. After addition of filtered S. pseudintermedius supernatants in culture cell media, MG63 cells, used as representative of non-professional phagocytic cells (NPPc), released a high level of LDH, indicating that the cytotoxicity was mainly mediated by secreted factors. Accordingly, we focused our attention on S. pseudintermedius toxins. In silico analysis found the presence of two PSMs (δ-toxin and PSMε) as well as Luk-I leukotoxin, the presence of which was confirmed by PCR in all clinical strains tested (n = 17). Recombinant Luk-I leukotoxin had no cytotoxic activity on NPPc but the ectopic expression of the CXCR2 receptor in U937 cells conferred cytotoxity to Luk-I. This is in agreement with the lack of Luk-I effect on NPPc and the previous report of Luk-I cytoxic activity on immune cells. Contrary to Luk-I, synthetic δ-toxin and PSMε had a strong cytotoxic activity on NPPc. The secretion of δ-toxin and PSMε at cytotoxic concentrations by S. pseudintermedius in culture supernatant was confirmed by HPLC-MS. In addition, the supplementation of such supernatants with human serum, known to inhibit PSM, induced a complete abolition of cytotoxicity which indicates that PSMs are the key players in the cytotoxic phenotype of NPPc. The results suggest that the severity of S. pseudintermedius infections is, at least in part, explained by a combined action of Luk-I that specifically targets immune cells expressing the CXCR2 receptor, and PSMs that disrupt cell membranes whatever the cell types. The present study strengthens the key role of PSMs in virulence of the different species belonging to Staphylococcus genus.